2020
DOI: 10.1155/2020/4062493
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Pain Management Education Programs (PMEPs): Do They Prepare Nurses to Deal with Patients’ Postoperative Pain?

Abstract: This is a report of a scoping review undertaken to obtain an overview of studies conducted on pain management education programs (PMEPs). The aim of this review was to describe existing research publications relating to PMEP to map how pain management practice training might directly influence surgical nurses in contributing to successful pain outcomes in patients. The initial search of electronic databases identified 40 articles according to the inclusion criteria and search strategy, which applied the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Our results demonstrate the complexity of implementing nursing strategies to improve nurses’ pain management skills. Nurses taking care of patients with pain recognised that this was part of their professional role, as mentioned in previous studies [ 5 , 6 , 7 , 8 , 9 , 12 ]. Nurses reported partnering with a ‘multidisciplinary team’ for problem-solving while caring for patients in recovery surgery.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our results demonstrate the complexity of implementing nursing strategies to improve nurses’ pain management skills. Nurses taking care of patients with pain recognised that this was part of their professional role, as mentioned in previous studies [ 5 , 6 , 7 , 8 , 9 , 12 ]. Nurses reported partnering with a ‘multidisciplinary team’ for problem-solving while caring for patients in recovery surgery.…”
Section: Discussionmentioning
confidence: 82%
“…Samarkandi [ 4 ], and Jaleta, Tuji, and Wake [ 5 ] have focused on pain management related to ineffective nursing strategies. Inefficiencies exist in multidisciplinary collaborations, the development of innovative knowledge and training by healthcare teams, and the recognition of individual differences in the delivery of pain management services [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review (Chatchumni, Eriksson, & Mazaheri, 2020 ) showed that PMEP utilizes diverse methods, including computer-based simulation, web-based facilitation, and video materials for educating nursing students. These methods improve nurses’ competence by enhancing their critical thinking, leadership, patient management, and health-promotion skills.…”
Section: Introductionmentioning
confidence: 99%
“…These methods improve nurses’ competence by enhancing their critical thinking, leadership, patient management, and health-promotion skills. The literature review suggested that PMEPs can help promote new opportunities for collaboration in multidisciplinary team projects (Chatchumni, Eriksson, & Mazaheri, 2020 ).…”
Section: Introductionmentioning
confidence: 99%